IMPLEMENTASI PEMBELAJARAN SAINS AUD MELALUI PERMAINAN TERAPUNG DAN TENGGELAM - Hidayatu Munawaroh (Kopertais Wilayah X Jawa Tengah, 2017)
The research is motivated by scientië c learning which was given by the teacher wasless attractive, monotonous, even using the manufactured game and toy that tended to be practically. The purpose of this research is to know how the scientië c learning implementation through ì oat and sink game in learning. The type of the research is descriptive research which uses qualitative approach. The result of the research is about the given scientië c learning by the teacher has adjusted with the theme and the sub theme, the method which is used by the teacher in scientië c learning has been able to develop the scientië c ability of children such as using experiment method. The obstacle is the teachers’ creativeness in designing scientië c activity.